Un document ancien sur l’urbanisme au Mzab - Cuperly, Pierre (Revue de l'Institut des Belles Lettres Arabes, 1981)
Arabic text and translation of the last chapter (112-118) of the third part of Kitāb Uṣūl al-Arāḍīn by Abū ‘l-ʿAbbās Aḥmad b. Abī ʿAbdl. Muḥ. b. Abī Bakr [al-Nafūsī]. Mainly on irrigation.
Keywords: Urbanisme -- Mzab

Le M'zab, espace et société - Benyoucef, Brahim (Acta Geographica, 1981)
Keywords: Urbanisme -- Mzab